2021
DOI: 10.3390/galaxies9020029
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Spiral Structure in a Multi-Component Milky Way-Like Galaxy

Abstract: Using recent observational data, we construct a set of multi-component equilibrium models of the disk of a Milky Way-like galaxy. The disk dynamics are studied using collisionless-gaseous numerical simulations, based on the joined integration of the equations of motion for the collision-less particles using direct integration of gravitational interaction and the gaseous SPH-particles. We find that after approximately one Gyr, a prominent central bar is formed having a semi-axis length of about three kpc, toget… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 135 publications
0
8
0
Order By: Relevance
“…Long periodic arms in spiral galaxies are well known, and they also exists in our Milky Way disk galaxy -for a review, see Vallée (2017b). Four main models compete for the formation of long spiral arms: density wave, tidal waves from a passing galaxy, Lyapunov tubes from the Galactic nucleus, dynamic transient waves, etc (see Khrapov et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Long periodic arms in spiral galaxies are well known, and they also exists in our Milky Way disk galaxy -for a review, see Vallée (2017b). Four main models compete for the formation of long spiral arms: density wave, tidal waves from a passing galaxy, Lyapunov tubes from the Galactic nucleus, dynamic transient waves, etc (see Khrapov et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We are interested in the influence of resonances with a bar outside the bar region; therefore, the stellar spatial distribution was generated outside four kpc using 10 6 particles and assuming the commonly accepted exponential density distribution law ∝ exp{−r/r d }, where r d is the radial scale length of the Galactic thin disk. There is a fairly large spread of the measured values of r d ranging from two to four kpc [35][36][37][38]. Following Jurić et al [39], we choose in this paper the value of r d = 2.5 kpc.…”
Section: Initial Distributionmentioning
confidence: 99%
“…We adopt the values of the velocity dispersions of particles in the solar neighborhood σ R , σ φ , σ Z equal to 31, 20 and 11 km s −1 Vieira et al [32]. The dependence of the velocity dispersion of particles on the radius was adopted in the form σ R = σ R,0 / exp(r/7.4 [ kpc]), taken from Khrapov et al [38], Tiede and Terndrup [42] where σ R,0 = 93 km s −1 to satisfy the observed value of the velocity dispersion in the solar neighborhood of σ R = 31 km s −1 . The azimuthal velocity dispersion was set using the equilibrium condition for the collisionless disk [38]:…”
Section: Initial Distributionmentioning
confidence: 99%
“…We used mathematical and corresponding numerical models of the dynamics of multicomponent galaxies, which are described in the works [93][94][95][96]. Gas movement was based on hydrodynamic equations: ∂ϱ ∂t…”
Section: Minor-merger Modelmentioning
confidence: 99%
“…The equation of state of an ideal gas with the adiabatic exponent γ = 5/3 closes the system of Equations ( 1)-(3). We used the SPH method to numerically integrate the Equations ( 1)-(3) [93][94][95][96], which has some advantages for modeling interacting multi-component galaxies. Firstly, it is possible to model both the collisional component (gas) and collisionless subsystems (stars and dark matter) in the same way, which is convenient when calculating the gravitational force.…”
Section: Minor-merger Modelmentioning
confidence: 99%